America and Enlightenment constitutionalism - McDowell, Gary L., 1949-; O'Neill, Johnathan G. (Johnathan George) (Studies of the Americas., 2006)
America and Enlightenment Constitutionalism shows in detail the Enlightenment origin of the U.S. Constitution. It provides vivid analysis of how the Enlightenment's basic ideas were reformulated in the context of America. It is particularly successful in bringing out the competing strains of Enlightenment thought and of articulating crucial Enlightenment concepts of public opinion, equality, public reason, legislature and judiciary, revolution, law, and the people in their American context. The collection is timely given contemporary debates between republicans and liberals about constitutional interpretation which are addressed throughout.